Assessing the reasons of Al-Qaeda$1 (Bs survival / s - M. Sheharyar Khan ([Place of publication not identified] : [Ankara University, Faculty of Political Science], 2013)
Summary: (3z(BOver a decade has passed since the United States launched the global (3z(Bwar on terror(3y (Bin the aftermath of tragic September 11 incident, yet the defeat of Al-Qaeda seems a for cry. This pre-emptive war, spread across the globe, is falling short of achieving its goals as the threat of Al-Qaeda to the security of the US and other allied countries is still very much alive. This global war seems to have no definitive end. This paper argues that the lack of synergy in the global alliance between the US and Muslim countries, where Al-Qaeda has found safe havens$1! =(3y$1 (B(page 167).s
Caption title.
(3z(BVolume 43 (2013)(3y$1 (Bat head of title.s
(3z(BThe Turkish yearbook of international relations(3y$1 (Bat head of pages.s
(3z(BVol.44 (2013)(3y$1 (Bat head of pages.s
Includes bibliographical references.
124
Keywords: Terrorism; Al-Qaeda organization; Taliban; Taliban -- Afghanistan; Terrorism -- Prevention; Terrorism -- History; War on Terrorism, 2001-2009.; Afghan War, 2001-.; Afghanistan -- Foreign relations